Signs of new housing bubble in many OECD countries: Lower risk in Germany - Konstantin A. Kholodilin; Claus Michelsen (DIW Weekly Report, 2018)
Ten years after the worldwide financial and economic crisis was triggered by the American real estate market, real estate prices are rising around the globe. Concerns about a new housing bubble are growing. The present report based on OECD data for 20 countries demonstrates that this concern is not unwarranted. In eight countries, including the United Kingdom and the USA, the evolution of real estate prices indicates that speculative investment behavior is at work. The continued high level of private household debt and low interest rates are evidence of a new bubble in those countries. There are also signs of this in Germany, but primarily in the country's largest cities. The risk of a nationwide housing price bubble is assumed to be lower in Germany due to the country's significantly lower level of private household debt. But since no suitable precautionary measures are in place, there is a need for action. Although it is now possible to cap lending, many market observers feel that the existing instruments could be reinforced. Capping the loan-to-household income ratio would be an especially desirable measure to prevent possible negative developments.
Keywords: E32; C33; C35; 330; speculative house price bubbles; explosive root test; panel logit model